Lung cancer mortality in the European cohort of titanium dioxide workers: a reanalysis of the exposure–response relationship. Issue 9 (2nd May 2022) - Guseva Canu, Irina; Gaillen-Guedy, Alan; Antilla, Ahti; Charles, Sandrine; Fraize-Frontier, Sandrine; Luce, Danièle; McElvenny, Damien Martin; Merletti, Franco; Michel, Cecile; Pukkala, Eero; Schubauer-Berigan, Mary K; Straif, Kurt; et al.
Abstract : Objectives: Animal bioassays have demonstrated convincing evidence of the potential carcinogenicity to humans of titanium dioxide (TiO2 ), but limitations in cohort studies have been identified, among which is the healthy worker survivor effect (HWSE). We aimed to address this bias in a pooled study of four cohorts of TiO2 workers. Methods: We reanalysed data on respirable TiO2 dust exposure and lung cancer mortality among 7341 male workers employed in TiO2 production in Finland, France, UK and Italy using the parametric g-formula, considering three hypothetical interventions: setting annual exposures at 2.4 (U.S. occupational exposure limit), 0.3 (German limit) and 0 mg/m 3 for 25 and 35 years. Results: The HWSE was evidenced. Taking this into account, we observed a positive association between lagged cumulative exposure to TiO2 and lung cancer mortality. The estimated number of lung cancer deaths at each age group decreased across increasingly stringent intervention levels. At age 70 years, the estimated number of lung cancer deaths expected in the cohort after 35-year exposure was 293 for exposure set at 2.4 mg/m 3, 235 for exposure set at 0.3 mg/m 3, and 211 for exposure set at 0 mg/m 3 . Conclusion: This analysis shows that HWSE can hide an exposure–response relationship. It also shows that TiO2 epidemiological data could demonstrate an exposure–effects relationship if analysed appropriately. More epidemiological studies and similar reanalyses of existing cohort studies are warranted to corroborate the human carcinogenicity of TiO2 . This human evidence, when combined with the animal evidence, strengthens the overall evidence of carcinogenicity of TiO2 .